Pengaruh Burnout terhadap Kesejahteraan Psikologis yang Dimoderasi oleh Hardiness pada Pembina Asrama di Pondok Pesantren - Khoiriah Barokah; Latipun Latipun; Nida Hasanati; Rini Yanti; Elpi Parida (Prodi PGMI STIT Al-Ittihadiyah Labuhanbatu Utara, 2026)
Psychological well-being is a crucial aspect for individuals, especially educators. However, a phenomenon has been identified in which dormitory supervisors in Islamic boarding schools (pesantren) experience a decline in psychological well-being, which is presumed to be influenced by Burnout. Therefore, a moderating factor is needed to reduce the negative impact of Burnout. This study aims to examine the role of Hardiness as a moderating variable in the relationship between Burnout and psychological well-being. This research employed a quantitative correlational design involving 197 dormitory supervisors from 20 modern Islamic boarding schools. Data were collected using the Maslach Burnout Inventory (MBI), the Psychological Well-Being Scale (PWBS), and the Short Hardiness Scale. Data were analyzed using moderation analysis with Hayes’ PROCESS Macro. The results indicated that Burnout had a significant negative effect on psychological well-being. Furthermore, Hardiness significantly moderated the relationship by weakening the negative impact of Burnout. Thus, individuals with higher Hardiness tend to maintain better psychological well-being despite experiencing Burnout.